Thickness-tunable growth of ultra-large, continuous and high-dielectric h-BN thin films. Issue 7 (15th January 2019) - Zhang, Dujiao; Wu, Feihong; Ying, Qi; Gao, Xinyu; Li, Nan; Wang, Kejing; Yin, Zongyou; Cheng, Yonghong; Meng, Guodong
Abstract : A thickness-tunable, ultra-large, continuous and high-dielectric h-BN films, achieved by optimizing LPCVD growth parameters, exhibit highly promising perspectives to develop electrically reliable 2D microelectronics with an ultrathin feature. Abstract : The outstanding thermal properties, mechanical properties and large optical bandgap of hexagonal boron nitride (h-BN) make it very attractive for various applications in ultrathin 2D microelectronics. However, the synthesis of large lateral size and uniform h-BN thin films with a high breakdown strength still remains a great challenge. Here, we comprehensively investigated the effect of growth conditions on the thickness of h-BN films via low pressure chemical vapor deposition (LPCVD). By optimizing the LPCVD growth parameters with electropolished Cu foils as the deposition substrates and developing customized "enclosure" quartz-boat reactors, we achieved thickness-tunable (1.50–10.30 nm) growth of h-BN thin films with a smooth surface (RMS roughness is 0.26 nm) and an ultra-large area (1.0 cm × 1.0 cm), meanwhile, the as-grown h-BN films exhibited an ultra-high breakdown strength of ∼10.0 MV cm −1, which is highly promising for the development of electrically reliable 2D microelectronic devices with an ultrathin feature.